القواعد المادية لمنازعات عقود قانون التجارة الدولية في الأنظمة العربية في إطار الاتفاقيات الدولية "دراسة مقارنة" - عبد الهادي زبيدة (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The current study aims at identifying the substantive and procedural rules of the international commercial contracts disputes in the Arabic regimes and agreements under the international conventions. In this context, the study considered the related international conventions. The study relied on the analytical descriptive comparative approach. This study reached results about the non- submission of the international commercial contracts to the “law of the Judge”. The contractors put in advance the arbitration clause in the international commercial contracts to the global nature of the international contract arising at the occurrence of conflict. Finally, among the most important findings was the focus of the Arabic legislations on the international agreements to be an integral part of the national law, and updating the systems to keep up with the international economic and commercial development. The current study consists of three chapters:- Introductory Chapter: Identification of the international trade contract. Chapter (I): The substantive rules that should be applied to the disputes of the International Trading Transactions Contracts. Chapter (II): The procedural rules of the conflicts relating to the International Trade Contracts.